Implementasi Program Evaluasi Pendidikan (Bimbingan Konseling) di Sekolah Dasar - Iqbal, Muhammad; Margolang, Ade Irvan; Alamsyahdana, Azwar; Syahbanda Nst, M Rezi; Pras, Jogi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Basic education plays a crucial role in shaping the academic and behavioral foundations of children worldwide. Amidst challenges such as early onset social and psychological issues, guidance and counseling in elementary schools are pivotal in providing the necessary support for the holistic development of students. This article systematically reviews literature concerning the implementation and evaluation of elementary school guidance and counseling programs. It focuses on evaluation methodologies, outcomes measured, and factors influencing successful implementation. The studies reviewed span various global contexts, exploring diverse approaches and practices in evaluating counseling programs. Key findings reveal varying evaluation methods utilized, encompassing both qualitative and quantitative techniques to gauge the programs' impact on students. Evaluation outcomes underscore improvements in academic performance, enhancement of social skills, and advancements in students' mental well-being. Critical factors contributing to successful implementation include strong school leadership, adequate resource allocation, and active parental engagement in the counseling process.